Brand Awareness as a Determinant of Purchase Intention: Evidence from Aquviva Bottled Water Consumers in Jayapura City - Indra Eka Wardana Toii (Sean Institute, 2026)
Competition in the bottled water industry in eastern Indonesia is increasingly fierce, requiring companies to increase brand awareness to influence consumer purchasing intention. Brand awareness is an important factor that can drive purchase intention, especially for products with a low level of involvement such as mineral water. This study aims to analyze the effect of brand awareness on the purchase intention of Aquviva mineral water products among consumers in Jayapura City. The research method used is quantitative and data were collected through distributing questionnaires to consumers who are aware of Aquviva products in Jayapura City. The sampling technique used was purposive sampling using SmartPLS 4.0. The results showed that brand awareness has a positive and significant effect on the purchase intention of Aquviva mineral water products. This finding indicates that the higher the level of consumer awareness of the Aquviva brand, the higher the consumer's purchase intention. This study is expected to be a reference for companies in designing marketing strategies that focus on increasing brand awareness to encourage consumer purchase intention.